Porous carbon material, preparation method thereof and battery

By preparing porous carbon materials with suitable particle size and specific surface area, and through gradient carbonization treatment, the problem of limited performance improvement of existing silicon carbon anode materials in power batteries is solved, and better silicon deposition and electrochemical performance are achieved.

CN119822368APending Publication Date: 2025-04-15WUHAN BISIDI BATTERY MATERIAL CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202510021091.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The performance improvement of existing silicon-carbon anode materials in power batteries is limited, especially in terms of silicon deposition structure and cycling performance.

Method used

A porous carbon material is provided, with a particle size D50 of 4 to 25 μm, a specific surface area of ​​1000 to 2500 m2/g, and a total pore capacity of 0.5 to 1.2 cm3/g. It is prepared by gradient carbonization treatment and used as a skeleton material for silicon deposition.

Benefits of technology

The porous carbon material is conducive to silicon deposition and improves the structural stability and electrochemical properties of the silicon carbon anode material, including improved specific capacity and cycling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822368A_ABST
    Figure CN119822368A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon material, a preparation method thereof and a battery, and belongs to the field of battery materials. The particle size D50 of the porous carbon material is 4-25 [mu] m, the specific surface area measured by a multi-point BET method is 1000-2500m < 2 > / g, and the total pore volume is 0.5-1.2 cm < 3 > / g. The porous carbon material has the particle size, the specific surface area and the total pore volume in the range, has good structural stability, is beneficial to silicon deposition, improves the structural stability of the silicon-carbon negative electrode material after silicon deposition, and improves the capacity and the cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrode materials, and in particular to a porous carbon material suitable for silicon deposition, a preparation method thereof, and a battery. Background Art

[0002] The application of silicon-carbon negative electrode materials in the field of power batteries is increasing, and the annual output has exceeded the thousand-ton level, and it is expected to gradually move towards the ten-thousand-ton scale. Silicon negative electrode materials have developed four generations of products in the process of iterative evolution over the years: from the first generation of sand-ground silicon carbon, the second generation of coated silicon oxygen, the third generation of pre-lithium pre-magnesium silicon oxygen and the latest generation of vapor-deposited silicon carbon. Among them, the latest generation of vapor-deposited silicon carbon is a battery negative electrode material obtained by uniformly depositing silicon nanoparticles inside the skeleton of a porous carbon material. And compared with traditional negative electrode materials such as silicon oxygen and ground silicon carbon, the use of vapor-deposited silicon carbon has significantly improved the first-cycle efficiency, energy density, cycle performance, cell expansion and other performance of the battery.

[0003] As the skeleton material of silicon-carbon negative electrode material, the structure of porous carbon material will directly affect silicon deposition, thereby affecting the performance of the final silicon-carbon negative electrode material. Summary of the invention

[0004] In view of this, the present application provides a porous carbon material and a preparation method thereof, and a battery, aiming to provide a porous carbon material that is conducive to silicon deposition and improves the performance of silicon-carbon negative electrode materials.

[0005] The embodiment of the present application is implemented by providing a porous carbon material, wherein the particle size D50 of the porous carbon is 4 to 25 μm, and the specific surface area measured by the multi-point BET method is 1000 to 2500 m 2 / g -1 , the total pore volume is 0.5~1.2cm 3 / g. .

[0006] In some embodiments, the porous carbon material has a porous structure; wherein the volume proportion of micropores with a pore size less than or equal to 2 nm calculated by the T-plot method is ≥ 60%; and / or,

[0007] The pore volume of macropores with a pore diameter greater than 5 nm accounts for ≤1%.

[0008] In some embodiments, the nitrogen adsorption isotherm satisfies V1 / V2=1-1.5, wherein V1 is the gas adsorption amount at a relative pressure of P / P0=0.8-0.99, and V2 is the gas adsorption amount at a relative pressure of P / P0=0.01-0.2.

[0009] In some embodiments, the most probable pore size distribution calculated by the BJH method based on the nitrogen adsorption isotherm is 0.1-2 nm; and / or,

[0010] The porous carbon material is a spherical or quasi-spherical particle; and / or,

[0011] The carbon source of the porous carbon material is starch or modified starch.

[0012] Accordingly, the present application also provides a method for preparing a porous carbon material, comprising:

[0013] providing a mixture of a carbon source precursor and an activator;

[0014] The mixture is subjected to a carbonization treatment, wherein the carbonization treatment is a gradient carbonization treatment including a first stage and a second stage, and the insulation temperature of the second stage is 150 to 900° C. higher than the insulation temperature of the first stage.

[0015] In some embodiments, the first stage of the insulation temperature is 100-600° C.; and / or,

[0016] The first stage of heat preservation time is 0.5 to 12 hours; and / or,

[0017] The temperature of the second stage is 750-1000° C.; and / or,

[0018] The insulation time of the second stage is 1 to 12 hours.

[0019] In some embodiments, the carbon source precursor includes starch and / or modified starch; wherein the modification method of the modified starch includes one or more of physical modification, chemical modification, and enzyme modification; and / or,

[0020] The particle size D50 of the carbon source precursor is 4 to 25 μm.

[0021] In some embodiments, the physical modification comprises one or more of wet heat treatment, ball milling treatment, microwave treatment, and ultrasonic treatment of the starch; and / or,

[0022] The chemical modification includes one or more of esterification modification, etherification modification, cross-linking modification and oxidation modification on the starch; and / or,

[0023] The enzyme-modified starch obtained by enzyme modification includes one or more of cyclodextrin, maltodextrin, and amylose; and / or,

[0024] The carbon source precursor is obtained by pre-carbonizing the starch and / or the modified starch.

[0025] In some embodiments, the esterified starch obtained by esterification modification includes one or more of alkenyl succinate starch, starch acetate, maleate starch, succinate starch, starch xanthate, starch amino acid methyl ester, starch sulfosuccinate, starch sulfate, starch nitrate, starch selenate, and starch phosphate; and / or,

[0026] The etherification modification is to treat the starch with an etherifying agent, wherein the etherifying agent includes one or more of ethylene oxide, propylene oxide, dimethyl sulfate, propylene chloride, ethyl chloride, methyl chloride, benzyl chloride, and monochloroacetic acid; and / or,

[0027] The cross-linking modification is to use a cross-linking agent to carry out a cross-linking reaction with starch, wherein the cross-linking agent includes one or more of epichlorohydrin, phosphorus oxychloride, sodium trimetaphosphate, citric acid, malic acid, glutaraldehyde, sodium polyphosphate, and isocyanate; and / or,

[0028] The oxidative modification is to oxidize the starch using an oxidant, wherein the oxidant includes one or more of hydrogen peroxide, sodium hypochlorite, and potassium permanganate; and / or,

[0029] The pre-carbonization treatment is carried out at a holding temperature of 280 to 2000° C.; and / or

[0030] The pre-carbonization treatment has a heat preservation time of 1 to 10 hours; and / or,

[0031] The atmosphere of the pre-carbonization treatment is an inert atmosphere.

[0032] Correspondingly, the present application also provides a battery, which includes a negative electrode material, and the negative electrode material includes a porous carbon material and silicon particles, and at least part of the silicon particles are distributed in the pores of the porous carbon material; wherein the porous carbon material is the above-mentioned porous carbon material, or is the negative electrode material prepared by the above-mentioned preparation method.

[0033] The porous carbon material of the present application has a particle size D50 of 4 to 25 μm and a specific surface area of ​​1000 to 2500 m 2 / g, total pore volume is 0.5~1.2cm 3 The porous carbon material of the present application has a particle size, specific surface area and total pore volume within the above range, and while having good structural stability, it is also conducive to silicon deposition, improves the structural stability of the silicon-carbon negative electrode material after silicon deposition, and improves the capacity and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 A schematic diagram of a process for preparing a porous carbon material according to an embodiment of the present invention;

[0036] Figure 2 is the SEM image of the porous carbon of Example 1;

[0037] Figure 3 is the isothermal adsorption diagram of the porous carbon of Example 1;

[0038] Figure 4 This is the isothermal adsorption diagram of the porous carbon of Comparative Example 1. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to".

[0040] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0041] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0042] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0043] The present application provides a porous carbon material, wherein the particle size D50 of the porous carbon is 4 to 25 μm, and the specific surface area measured by the multi-point BET method is 1000 to 2500 m 2 / g, total pore volume is 0.5~1.2cm 3 / g.

[0044] The particle size D50 can be 4-8 μm, 8-15 μm, 15-20 μm, 20-25 μm, etc., and the specific surface area can be 1000-1500 m 2 / g, 1500~2000m 2 / g, 2000~2500m 2 / g, etc., and the total pore volume can be specifically 0.5 to 0.8 cm 3 / g, 0.8~1.0cm 3 / g, 1.0~1.2cm 3 / g, etc., and of course, it can also be other values ​​within the above range, which are not limited here. Among them, the total pore volume can be obtained or calculated by nitrogen adsorption isotherm.

[0045] The porous carbon material of the present application has a particle size, specific surface area and total pore volume within the above range. While having good structural stability itself, it is also beneficial to silicon deposition, improving the structural stability of the silicon-carbon negative electrode material after silicon deposition, and improving the capacity and cycle performance.

[0046] In one embodiment, the porous carbon material is a spherical or quasi-spherical particle, and the particle surface is smooth without obvious breakage or cracks. Further, its carbon source is starch or modified starch. In this embodiment, the porous carbon material prepared by using starch or modified starch as a carbon source can have particles with good sphericity, and the corresponding performance is improved by modifying the raw material end.

[0047] The porous carbon material of the present application has a porous structure, specifically including micropores (pore diameter is less than or equal to 2 nm), mesopores (pore diameter is 2 to 50 nm) and macropores (pore diameter is greater than 50 nm).

[0048] In one embodiment, the most probable pore size distribution calculated by the BJH method according to the nitrogen adsorption isotherm is 0.1-2 nm, specifically 0.1-0.2 nm, 0.2-0.5 nm, 0.5-0.8 nm, 0.8-1.0 nm, 1.0-1.2 nm, 1.2-1.5 nm, 1.5-1.8 nm, 1.8-2.0 nm, etc. Of course, it can also be other values ​​within the above range, which are not limited here. The porous carbon material has a pore structure with the most probable pore size distribution, which is conducive to silicon deposition and limits the particles of deposited silicon, ultimately improving the cyclic stability of silicon carbon and reducing the expansion of silicon particles; in addition, for the structure of the porous carbon itself, the above pore structure helps to increase the surface area without causing serious damage to the main structure.

[0049] In one embodiment, the pore volume of micropores with a pore size less than 2 nm calculated by the T-plot method is ≥70%, specifically 70% to 99.9%, 80% to 99.9%, 90% to 99.9%, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0050] In one embodiment, the pore volume proportion of macropores with a pore size greater than 5 nm is ≤1%, which can be specifically 0.01% to 0.05%, 0.05% to 0.1%, 0.1% to 0.5%, 0.5% to 1%, etc. Of course, it can also be other values ​​within the above range, which are not limited here. Specifically, the pore volume proportion of macropores can be calculated by the pore volume proportion of micropores and mesopores. In this embodiment, the porous carbon material mainly includes micropores and mesopores, and contains only very few macropores, which is beneficial to maintaining the bulk structure and its stability, has good compressive strength, and can provide more active sites for the deposition of nano-silicon.

[0051] In one embodiment, in the nitrogen adsorption isotherm, V1 / V2=1~1.5, wherein V1 is the gas adsorption amount at the relative pressure P / P0=0.8~0.99, and V2 is the gas adsorption amount at the relative pressure P / P0=0.01~0.2. Specifically, V1 / V2 can be 1~1.1, 1.1~1.2, 1.2~1.3, 1.3~1.4, 1.4~1.5, etc., and of course, it can also be other values ​​within the above range, which is not limited here. In this embodiment, the ratio of gas adsorption, i.e., V1 / V2, is within the above range, which helps to maintain the structural strength of the porous carbon body while providing more active sites for the deposition of nano-silicon, thereby improving the cycle stability and specific capacity of the silicon-carbon negative electrode material.

[0052] The present application also provides a method for preparing a porous carbon material, see Figure 1 , Figure 1 This is a schematic flow chart of an embodiment of a method for preparing a porous carbon material provided in the present application, which specifically includes the following steps:

[0053] Step S11: providing a mixture of a carbon source precursor and an activator;

[0054] Step S12: subjecting the mixture to carbonization treatment, wherein the carbonization treatment is a gradient carbonization treatment including a first stage and a second stage, and the temperature of the second stage is 150-900° C. higher than the temperature of the first stage.

[0055] In the present application, by subjecting a mixture of a carbon source precursor and an activator to at least two stages of gradient carbonization treatment, including a first stage and a second stage, it helps to increase the specific surface area of ​​the porous carbon, while significantly increasing the number of micropores and inhibiting the formation of macropores, thereby preparing the above-mentioned porous carbon material with a large specific surface area and a controllable micropore / mesopore ratio.

[0056] Compared with conventional porous carbon material preparation methods such as hydrothermal carbonization, template method and vapor deposition method, the preparation method provided in this application has the advantage of simple process and can be prepared by gradient carbonization. Specifically, the porous carbon material obtained by hydrothermal carbonization generally presents a relatively regular spherical morphology, but a high-pressure environment is required during the experiment, which has high requirements for equipment, lengthy and complex processes, and great difficulty in industrialization. The vapor deposition method has the problems of high energy consumption, high cost, and difficulty in regulating the morphology of porous carbon. The porous carbon directly obtained by the template method has a variety of morphologies. Unreasonable control of experimental process parameters such as activator ratio and carbonization temperature may cause the obtained porous carbon to present irregular blocks, spherical breakage, collapse of pore structures such as micropores and mesopores, and inability to subsequently deposit silicon.

[0057] In step S11:

[0058] The carbon source precursor includes starch and / or modified starch. The starch is a natural starch derived from plants, which is generally composed of amylose and amylopectin, and the composition ratio of amylose and amylopectin in different plants is different, which also leads to certain differences in the structure and properties of different starches. Specifically, the source of starch can be cereal foods such as corn, rice and millet, tuber foods such as sweet potatoes, purple sweet potatoes and potatoes, and cereal foods such as red beans and mung beans.

[0059] The modification method of the modified starch may include one or more of physical modification, chemical modification, and enzyme modification. It is understandable that the modified starch may be a modified starch obtained by one modification method, or may be a composite modified starch obtained by two or more composite treatments.

[0060] Specifically, physical modification includes modifying starch by physical means such as wet heat treatment, ball milling treatment, microwave treatment, and ultrasonic treatment.

[0061] Chemical modification mainly refers to various modifications that involve chemical reactions on the more alcohol hydroxyl groups in starch molecules, which may include one or more of esterified starch, etherified starch, cross-linked starch, and oxidized starch.

[0062] The esterified starch includes organic acid ester starch and inorganic acid ester starch. It can be understood that the organic acid ester starch is obtained by esterifying the hydroxyl groups in the starch with organic acids, such as alkenyl succinate starch, starch acetate, maleate ester starch, succinate starch, starch xanthate, starch amino acid methyl ester, starch sulfonates, etc.; the inorganic acid ester starch is obtained by esterifying the hydroxyl groups in the starch with inorganic acids, such as starch sulfate, starch nitrate, starch selenate, starch phosphate, etc.

[0063] In a specific embodiment, the preparation method of the esterified starch is: drying the natural starch at 100-200°C for 0.5-20h, and then mixing with the esterifying agent for reaction, wherein the amount of the esterifying agent added is 5-20wt% of the dried starch, the temperature of the mixing reaction is 100-180°C, and the time is 1-10h.

[0064] Etherified starch is a starch derivative in which the glycosidic bond or active hydroxyl group in starch is connected to the etherifying agent through oxygen atoms, and common ones include hydroxyalkyl starch, carboxymethyl starch and cationic starch, etc. The etherifying agent can include one or more of ethylene oxide, propylene oxide, dimethyl sulfuric acid, propylene chloride, ethyl chloride, methyl chloride, benzyl chloride, hydrocarbons containing some bromine and iodine, organic amine compounds containing epoxy groups or halogenated hydrocarbon groups (such as tertiary amine alkyl, quaternary amine alkyl), monochloroacetic acid, etc.

[0065] Cross-linked starch is a starch derivative formed by the reaction of a large number of hydroxyl groups on starch molecules with a cross-linking agent having a difunctional group or a multifunctional group to form a new chemical bond (generating a diether bond, a diester group, etc.), and cross-linking the starch. Specifically, the cross-linking agent may include one or more of epichlorohydrin (ECH), phosphorus oxychloride, sodium trimetaphosphate (STMP), citric acid, malic acid, glutaraldehyde, sodium polyphosphate, isocyanate, etc. Commonly used cross-linking methods include wet cross-linking, ultrasonic and microwave assisted cross-linking, etc.

[0066] Oxidized starch refers to a modified starch obtained by oxidation of starch with an oxidant, wherein the oxidant may include one or more of hydrogen peroxide, sodium hypochlorite, potassium permanganate, and the like.

[0067] Enzyme-modified starch refers to modified starch obtained by treating starch with various enzymes, including cyclodextrin, maltodextrin, amylose, etc.

[0068] The complex modified starch may include one or more of cross-linked etherified starch, esterified etherified starch, esterified oxidized starch, oxidized etherified starch, and the like.

[0069] In another embodiment, the carbon source precursor is obtained by pre-carbonization treatment of the starch and / or the modified starch. Specifically, the insulation temperature of the pre-carbonization treatment is 280-2000°C, the insulation time is 1-10h, the heating rate is 1-10°C / min, and the atmosphere is an inert atmosphere. Among them, the starch and the modified starch can refer to the relevant description in the previous text, such as esterified starch, etherified starch, cross-linked starch, oxidized starch, etc.

[0070] The particle size D50 of the carbon source precursor is 4-25 μm, specifically 4-20 μm, 10-20 μm, 15-20 μm, etc., and of course, it can also be other values ​​within the above range, which is not limited here. The particle size of the carbon source precursor within this range can increase the contact area with the activator, improve the mixing uniformity, and improve the activation effect.

[0071] The activator includes one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and zinc chloride.

[0072] In the mixture, the mass ratio of the carbon source precursor to the activator is 1:10 to 10:1, specifically 1:10 to 1:5, 1:5 to 1:1, 1:1 to 5:1, 5:1 to 10:1, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0073] In a specific embodiment, before step S11, the step further includes: mixing the carbon source precursor and the activator at a high speed, and the mixing speed may be 100-1000 rpm.

[0074] In step S12:

[0075] In some embodiments, the insulation temperature of the first stage is 100-600°C, specifically 150-400°C, 150-350°C, 200-350, 200-300°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0076] In some embodiments, the insulation time of the first stage is 0.5 to 12 hours, specifically 0.5 to 10 hours, 0.5 to 8 hours, 1 to 8 hours, 1 to 5 hours, 1 to 3 hours, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0077] In some embodiments, the insulation temperature of the second stage is 750-1000°C, specifically 800-1000°C, 800-950°C, 800-900°C, 850-900°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0078] In some embodiments, the insulation time of the second stage is 1 to 12 hours, specifically 1 to 10 hours, 1.5 to 10 hours, 1.5 to 8 hours, 2 to 8 hours, 3 to 6 hours, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0079] In one embodiment, the carbonization treatment is specifically to transfer the mixture into a sagger and place it in a heating device for heating. It can be heated from room temperature to the temperature of the first stage and kept warm for a period of time, and then continue to heat up to the insulation temperature of the second stage and keep warm for a preset time, and then cool to room temperature.

[0080] After step S12, the method further includes: crushing the carbonized material obtained by the carbonization treatment to a D50 of 4 to 25 μm, and then washing it to a neutral state (i.e., a pH of 6 to 7) to completely remove the unreacted activator and its intermediates to avoid affecting subsequent deposition.

[0081] The cleaning agent used in the cleaning treatment is one or more of water or acid solution. The water may be tap water, deionized water, pure water, ultrapure water, etc. The acid solution may be a mixed acid solution formed by one or more of aqueous solutions of hydrochloric acid, nitric acid, hydrofluoric acid, and sulfuric acid, and the mass concentration may be 2% to 60%.

[0082] The cleaning process may be one or more of immersion, showering, etc. The cleaning process may be one or more times, such as multiple water cleaning, multiple acid cleaning, or multiple water and acid cleaning.

[0083] The present application also provides a silicon-carbon electrode material, the silicon-carbon electrode material comprising a porous carbon material and nano-silicon, wherein the nano-silicon is at least partially distributed in the pores of the porous carbon material, wherein the porous carbon material and its preparation refer to the description above, and are not described in detail here. The silicon-carbon electrode material can be used as an electrode active material in an electrode of an electrochemical device.

[0084] In one embodiment, a silicon-carbon negative electrode material is prepared by chemical vapor deposition, specifically, the porous carbon material powder provided in the present application is put into a feeding bin, and then the powder is conveyed into a vapor deposition furnace by positive pressure conveying, and a silane / nitrogen mixed gas is introduced under high temperature conditions of 400 to 550°C to thermally decompose and deposit silane in the porous carbon material. Subsequently, the temperature is raised to 550 to 700°C, and an acetylene / nitrogen mixed gas is introduced to thermally decompose and deposit acetylene on the surface of the silicon / carbon material. The entire deposition process takes about 8 to 12 hours. After the reaction is completed, screening and demagnetization are performed to finally obtain the silicon-carbon negative electrode material.

[0085] The present application also provides an electrochemical device, the electrochemical device comprising an electrode, the electrode comprising the silicon-carbon electrode material. Specifically, the electrochemical device may include a battery, a capacitor, and the like.

[0086] In a specific embodiment, the electrochemical device is a battery, and the negative electrode of the battery includes the silicon-carbon electrode material.

[0087] The technical scheme and technical effects of the present application are described in detail below through specific embodiments, comparative examples and experimental examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.

[0088] Example 1

[0089] Step 1: pretreating the starch to obtain pretreated starch with a D50 of 12.39 μm, wherein the specific steps of the pretreatment are: placing the natural corn starch in an oven at 140°C and drying it for 11 hours, mixing the dried starch and maleic anhydride in a double cone and performing an esterification reaction to obtain esterified starch, wherein the mass ratio of starch to maleic anhydride is 10:1, the esterification temperature is 100°C, and the time is 4 hours; placing the obtained esterified starch in a tubular furnace for pretreatment, heating it to 1300°C at a heating rate of 2°C / min under a nitrogen atmosphere, and keeping it warm for 3 hours.

[0090] Step 2: Mix the pretreated starch and potassium hydroxide at a mass ratio of 1:2 at a high speed at a speed of 500 rpm;

[0091] Step 3: The mixed pre-carbonized esterified starch and potassium hydroxide are transferred to a tube furnace for gradient carbonization treatment, with the first stage temperature at 150°C for 2h and the final carbonization temperature at 800°C for 2h;

[0092] Step 4: After the carbonization treatment is completed, the pre-carbonized esterified starch-based porous carbon is initially obtained, and water is added to wash it repeatedly until the product becomes neutral.

[0093] Example 2

[0094] Similar to Example 1, the difference is that in step 3, the temperature of the first stage is 600° C., 0.5 h, and the final carbonization temperature is 800° C., 2 h.

[0095] Example 3

[0096] Similar to Example 1, the difference is that in step 3, the temperature of the second stage is 750° C. and the time is 12 hours.

[0097] Example 4

[0098] Similar to Example 1, the difference is that in step 3, the temperature of the second stage is 1000° C. and the time is 1 hour.

[0099] Example 5

[0100] Similar to Example 1, the difference is that in step 2, the mass ratio of pretreated starch to potassium hydroxide is 1:10.

[0101] Example 6

[0102] Similar to Example 1, the difference is that in step 2, the mass ratio of pretreated starch to potassium hydroxide is 10:1.

[0103] Example 7

[0104] Similar to Example 1, the difference is that in step 1, only esterification treatment is performed to obtain esterified starch, and no pre-carbonization treatment is performed.

[0105] Example 8

[0106] Similar to Example 1, the difference is that step 1 is not performed, and step 2 and subsequent steps are directly performed using natural corn starch and an activator.

[0107] Example 9

[0108] Similar to Example 1, except that in step 1, the pre-carbonization temperature is 280° C. and the time is 10 h.

[0109] Example 10

[0110] Similar to Example 1, the difference is that in step 1, the pre-carbonization temperature is 2000° C. and the time is 1 hour.

[0111] Embodiment 11

[0112] Similar to Example 1, the difference is that in step 1, the pretreatment includes etherification and pre-carbonization, wherein the etherification step is: firstly dissolve sodium sulfate in water under heating conditions, the heating temperature is 50°C, and then disperse the starch in the sodium sulfate aqueous solution to form a suspension. A small amount of sodium hydroxide and propylene oxide are added to the suspension to react for 3 hours, and the atmosphere during the reaction stage is nitrogen. After the reaction is completed, a small amount of hydrochloric acid is used to adjust the pH to about 6, and then the etherified starch is obtained by centrifugation, washing with water and drying.

[0113] Example 12

[0114] Similar to Example 11, the difference is that in step 1, the pretreatment includes etherification, and no pre-carbonization is performed.

[0115] Embodiment 13

[0116] Similar to Example 1, the difference is that in step 1, the pretreatment includes cross-linking and pre-carbonization, wherein the cross-linking step is: firstly dissolve sodium trimetaphosphate in water, then add natural starch to the aqueous solution of sodium trimetaphosphate, the mass ratio of starch to sodium trimetaphosphate is 2:1, and a small amount of sodium hydroxide is added to adjust the pH to close to 10. Heat the reaction in a water bath at 40°C for 2 hours. After the reaction is completed, the product is filtered, washed and dried to obtain cross-linked starch.

[0117] Embodiment 14

[0118] Similar to Example 13, the difference is that in step 1, the pretreatment includes cross-linking, and no pre-carbonization is performed.

[0119] Comparative Example 1

[0120] Similar to Example 1, the difference is that in step 3, the temperature is directly kept at 800° C. for 2 hours.

[0121] Comparative Example 2

[0122] Similar to Example 1, the difference is that in step 3, the first stage temperature is 100°C, 2h, and the final carbonization temperature is 700°C, 2h.

[0123] Comparative Example 3

[0124] Similar to Example 1, the difference is that in step 3, the first stage temperature is 700°C, 2h, and the final carbonization temperature is 800°C, 2h.

[0125] Comparative Example 4

[0126] Similar to Comparative Example 1, the difference is that step 1 is not performed, and natural corn starch and an activator are directly used to perform step 2 and subsequent steps.

[0127] [test]

[0128] Figure 2 is the SEM image of the porous carbon of Example 1, Figure 2 It can be seen that the particles of the porous carbon material prepared in Example 1 have good sphericity, and the particle surface is smooth without obvious breakage or cracks.

[0129] The porous carbon materials prepared in various embodiments and comparative examples were tested. The test results are shown in Table 1. The specific test methods are as follows:

[0130] Particle size D50 test: Referring to GB / T 19077-2016 particle size distribution laser diffraction method, the particle size D50 was measured and obtained using the British Malvern Mastersizer2000E laser particle size analyzer.

[0131] The nitrogen adsorption test obtains the nitrogen adsorption isotherm, and the total pore volume is obtained or calculated through the nitrogen adsorption isotherm, as well as the specific surface area obtained by the BET method, the most probable pore size distribution calculated by the BJH method, the pore volume percentage of micropores with a pore size less than 2 nm, the pore volume percentage of macropores with a pore size greater than 5 nm, and the V1 / V2 value calculated by the T-plot method.

[0132] Table 1:

[0133]

[0134]

[0135] It can be seen from Table 1 that the carbonization adopts the first stage + second stage combined treatment, that is, the specific surface area of ​​the porous carbon material prepared by the BET method of Examples 1-14 is relatively high; the treatment temperature of the first stage is not in the range of 100-600°C and / or the temperature of the second stage is not in the range of 750-1000°C, that is, Comparative Examples 1-4, which will deteriorate the pore structure parameters of the porous carbon, including but not limited to specific surface area, total pore volume and most probable pore size distribution, such as causing a decrease in specific surface area, a decrease in the proportion of micropores, and a decrease in total pore volume.

[0136] Silicon-carbon preparation and half-cell preparation and testing

[0137] The porous carbon materials of the above embodiments and comparative examples are used as carbon skeletons to deposit silicon to obtain corresponding silicon-carbon materials. The specific steps are:

[0138] The silicon-carbon negative electrode material is prepared by chemical vapor deposition. The specific method is to put the porous carbon material powder into the feeding bin, and then send the powder into the vapor deposition furnace by positive pressure conveying. At a high temperature of 450°C, a silane / nitrogen mixed gas is introduced to pyrolyze and deposit silane in the porous carbon material. Subsequently, the temperature is raised to 600°C, and an acetylene / nitrogen mixed gas is introduced to pyrolyze and deposit acetylene on the surface of the silicon / carbon material. The entire deposition process takes about 8 hours. After the reaction is completed, the silicon-carbon negative electrode material is finally obtained by screening and demagnetization.

[0139] The obtained silicon-carbon negative electrode material was assembled into a half-cell for electrochemical performance testing. The specific steps were as follows: taking the corresponding silicon-carbon material obtained by depositing silicon on the porous carbon of the above-mentioned embodiment and comparative example, using it as an active material, mixing it with a binder and a conductive agent in a mass ratio of 8:1:1, applying a slurry, drying, and punching it into a circular electrode piece with a diameter of 8 mm, matching a metal lithium sheet to make a CR2025 button battery, the electrolyte being 1M LiPF6 / EC / DEC+10% FEC, and the data of the constant current charge and discharge test are summarized in Table 2.

[0140] Table 2 Electrochemical properties of silicon-carbon negative electrode materials

[0141]

[0142]

[0143] As can be seen from Table 2, the silicon-carbon negative electrode material is prepared by silicon deposition on the porous carbon obtained by the embodiment of this patent and electrochemical testing is performed. The silicon-carbon material shows good specific capacity, first efficiency and excellent cycle stability. It shows that the porous carbon of the embodiment has a good confinement effect on the nano-silicon particles, and effectively inhibits the expansion and pulverization of silicon during the charge and discharge process. It also further illustrates that the limitation of the pore structure-related parameters and experimental parameters of the porous carbon in this patent has a positive significance for improving the performance of silicon-carbon.

[0144] Compared with Example 1, Comparative Example 1 did not perform the first stage carbonization, that is, it was directly carbonized to 800°C in one step. The total pore volume and the most probable pore diameter of the obtained porous carbon were relatively large, the proportion of micropores was significantly reduced, and the proportion of macropores was increased. The porous carbon could not withstand the stress generated by the expansion of silicon particles during the charge and discharge process and then broke, which ultimately led to the relatively poor cycle stability of the silicon-carbon negative electrode material prepared after the deposition of silicon carbon.

[0145] Compared with Example 1, Comparative Examples 2 and 3 both use two-stage carbonization treatment, but the temperature range of the first stage or the second stage is not within the limit requirements of this patent, the total pore volume of porous carbon is relatively low, and the specific capacity of the silicon-carbon negative electrode made after silicon deposition is relatively small. Compared with Example 1, Comparative Example 4 uses natural starch to directly carbonize to 800°C in one step, the proportion of macropores is high, the porous carbon is easy to break, and the corresponding silicon-carbon negative electrode has poor cycle stability.

[0146] The porous carbon material, preparation method and battery provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A porous carbon material, characterized in that: The particle size D50 of the porous carbon is 4 to 25 μm, and the specific surface area measured by the multi-point BET method is 1000 to 2500 m 2 / g, total pore volume is 0.5~1.2cm 3 / g.

2. The porous carbon material according to claim 1, characterized in that The porous carbon material has a porous structure; wherein the volume proportion of micropores with a pore size of less than or equal to 2 nm calculated by the T-plot method is ≥ 60%; and / or, The pore volume of macropores with a pore diameter greater than 5 nm accounts for ≤1%.

3. The porous carbon material according to claim 1 or 2, characterized in that: The nitrogen adsorption isotherm satisfies V1 / V2=1-1.5, wherein V1 is the gas adsorption amount when the relative pressure P / P0=0.8-0.99, and V2 is the gas adsorption amount when the relative pressure P / P0=0.01-0.

2.

4. The porous carbon material according to any one of claims 1 to 3, characterized in that: The most probable pore size distribution calculated by the BJH method based on the nitrogen adsorption isotherm is 0.1 to 2 nm; and / or, The porous carbon material is a spherical or quasi-spherical particle; and / or, The carbon source of the porous carbon material is starch or modified starch.

5. A method for preparing a porous carbon material, characterized in that: include: providing a mixture of a carbon source precursor and an activator; The mixture is subjected to a carbonization treatment, wherein the carbonization treatment is a gradient carbonization treatment including a first stage and a second stage, and the insulation temperature of the second stage is 150 to 900° C. higher than the insulation temperature of the first stage.

6. The porous carbon material according to claim 5, characterized in that: The insulation temperature of the first stage is 100-600° C.; and / or, The first stage of heat preservation time is 0.5 to 12 hours; and / or, The second stage insulation temperature is 750-1000°C; and / or, The insulation time of the second stage is 1 to 12 hours.

7. The porous carbon material according to claim 5, characterized in that: The carbon source precursor includes starch and / or modified starch; wherein the modification method of the modified starch includes one or more of physical modification, chemical modification, and enzyme modification; and / or, The particle size D50 of the carbon source precursor is 4 to 25 μm.

8. The porous carbon material according to claim 7, characterized in that: The physical modification includes one or more of wet heat treatment, ball milling treatment, microwave treatment, and ultrasonic treatment on the starch; and / or, The chemical modification includes one or more of esterification modification, etherification modification, cross-linking modification and oxidation modification on the starch; and / or, The enzyme-modified starch obtained by enzyme modification includes one or more of cyclodextrin, maltodextrin, and amylose; and / or, The carbon source precursor is obtained by pre-carbonizing the starch and / or the modified starch.

9. The porous carbon material according to claim 8, characterized in that: The esterified starch obtained by esterification modification includes one or more of alkenyl succinate starch, starch acetate, maleate starch, succinate starch, starch xanthate, starch amino acid methyl ester, starch sulfosuccinate, starch sulfate, starch nitrate, starch selenate, and starch phosphate; and / or, The etherification modification is to treat the starch with an etherifying agent, wherein the etherifying agent includes one or more of ethylene oxide, propylene oxide, dimethyl sulfate, propylene chloride, ethyl chloride, methyl chloride, benzyl chloride, and monochloroacetic acid; and / or, The cross-linking modification is to use a cross-linking agent to carry out a cross-linking reaction with starch, wherein the cross-linking agent includes one or more of epichlorohydrin, phosphorus oxychloride, sodium trimetaphosphate, citric acid, malic acid, glutaraldehyde, sodium polyphosphate, and isocyanate; and / or, The oxidative modification is to oxidize the starch using an oxidant, wherein the oxidant includes one or more of hydrogen peroxide, sodium hypochlorite, and potassium permanganate; and / or, The pre-carbonization treatment is carried out at a holding temperature of 280 to 2000° C.; and / or The pre-carbonization treatment has a heat preservation time of 1 to 10 hours; and / or The atmosphere of the pre-carbonization treatment is an inert atmosphere.

10. A battery, characterized in that: The battery includes a negative electrode material, which includes a porous carbon material and silicon particles, and at least part of the silicon particles are distributed in the pores of the porous carbon material; wherein the porous carbon material is the porous carbon material described in any one of claims 1 to 4, or is the negative electrode material prepared by the preparation method described in any one of claims 5 to 9.

Citation Information

Cited By

  • Silicon-carbon negative electrode material based on spherical starch porous carbon and preparation method of silicon-carbon negative electrode material

    CN120039880A

  • A silicon-carbon negative electrode material based on spherical starch porous carbon and its preparation method

    CN120039880B

  • Method for preparing porous carbon through microwave synergistic chemical double-activation graded pore forming

    CN121247800A

  • High-pressure-resistant spherical porous carbon as well as preparation method and application thereof

    CN121342017A

  • Biomass-based carbon material as well as preparation method and application thereof

    CN121516866A